The Effect of Teaching Factory Implementation on The Competence and Readiness to Work of Students of the Catering Service Study Program at SMKN 2 Mojokerto - Permata, Tri Wahyuni Indah; Nurlaela, Luthfiyah; Ismawati, Rita; Rijanto, Tri (Universitas Malikussaleh, 2021)
This study aims to analyze the effect of implementing the teaching factory on readiness to work through the competence of students. This research was conducted at SMKN 2 Mojokerto. This research is an ex-post facto research. The population of this study were students of class XI and class XII of the catering service program at SMKN 2 Mojokerto, totaling 193 students. The research sampling technique was simple random sampling and calculated using the Slovin formula, so that the number of research samples was 130 students. The data analysis technique used path analysis. Research data collection uses a questionnaire instrument on the variables of teaching factory implementation and readiness to work, while for competence using tests and observation sheets. Before being distributed to research respondents, a validation test was first conducted on each research instrument. In line with the objectives, the results of the study show that: (1) the implementation of the teaching factory has a positive effect on the competence of students at SMKN 2 Mojokerto; (2) The implementation of the teaching factory has a positive effect on the readiness to work of the students at SMKN 2 Mojokerto; (3) The competence of students has a positive effect on the readiness to work of students at SMKN 2 Mojokerto; and (4) the implementation of the teaching factory has a positive effect on the readiness to work of students at SMKN 2 Mojokerto through the competence of students.